Multi-level Language Proficiency in Learning a non-Native Language - Utebalieva Г.Е.; Kaskabassova Х.С. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2018)
This article is dedicated to the question of how students with varying language abilities can acquire non-native language proficiency. The article gives an analytic overview of the work of students at various levels of language proficiency as they continue to study a non-native language. The overview is based on complex research that is currently being used by language teachers. An integrative approach to the study of the communicative and cognitive activity of a secondary language personality provides a new perspective on the study of foreign languages. The authors of the article propose a program with a complex approach to individualized study. Individual study gives participants the opportunity to optimize their work surrounding the acquisition of communicative and cognitive secondary language personality and allows them to achieve positive results